Radio as an effective tool for community mobilisation for eye health programs, a case study of the Mbarara University of Science and Technology, Department of Ophthalmology outreach program to Ntungamo district, rural south-western Uganda - Arunga, S.; Twinamasiko, A. (The Journal of Ophthalmology of Eastern, Central and Southern Africa, 2015)
To determine the most effective method of mobilizing the rural community to uptake cataract outreach services in Ntungamo district, south western Uganda. Methods: This was a community based prospective survey conducted in Ntungamo district, rural south western Uganda. Different methods were used to inform the local communities in the six sub regions in Ntungamo district about an ongoing University outreach program. These included; local radio announcements, announcements at places of worship, posters, word of mouth and referral from a previous outreach. One hundred and twenty five respondents were randomly selected from a total of 600 people who turned up for the service and enrolled into the study. Interviewer administered questionnnars were administered. The main interview question was how respondents had received information about a cataract outreach service coming to their area. Results were compiled and frequency tabulations were drawn. Results: The respondents reported that they received the information through radio announcements (85.6%), by word of mouth (10%), by posters (2%) and by referral from previous outreach (1%). The results were consistent across all the six sub regions in Ntungamo district. Conclusion: Radio announcements were the most effective method for mobilizing the community for uptake of cataract outreach services. Recommendation: Radio should be encouraged as a key tool for mobilizing communities to uptake health promotion services.
Keywords: Radio; Community mobilisation; Eye health programs; Mbarara University of Science and Technology